Proceedings 2018 Network and Distributed System Security Symposium 2018
DOI: 10.14722/ndss.2018.23204
|View full text |Cite
|
Sign up to set email alerts
|

Kitsune: An Ensemble of Autoencoders for Online Network Intrusion Detection

Abstract: Abstract-Neural networks have become an increasingly popular solution for network intrusion detection systems (NIDS). Their capability of learning complex patterns and behaviors make them a suitable solution for differentiating between normal traffic and network attacks. However, a drawback of neural networks is the amount of resources needed to train them. Many network gateways and routers devices, which could potentially host an NIDS, simply do not have the memory or processing power to train and sometimes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
415
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 774 publications
(426 citation statements)
references
References 32 publications
1
415
0
10
Order By: Relevance
“…Autoencoders have been used for anomaly and intrusion detection before [41], [42]. The differences between this work and [41] are that in our research (1) AEs are applied to raw physical signals without statistical feature extraction, and (2) AEs are applied to the frequency domain.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoencoders have been used for anomaly and intrusion detection before [41], [42]. The differences between this work and [41] are that in our research (1) AEs are applied to raw physical signals without statistical feature extraction, and (2) AEs are applied to the frequency domain.…”
Section: Related Workmentioning
confidence: 99%
“…Autoencoders have been used for anomaly and intrusion detection before [41], [42]. The differences between this work and [41] are that in our research (1) AEs are applied to raw physical signals without statistical feature extraction, and (2) AEs are applied to the frequency domain. We extend the research in [42] by applying AEs to cyber attack detection in time series, combining control, status and raw physical data, as well as applying AEs to the frequency domain.…”
Section: Related Workmentioning
confidence: 99%
“…These models do not require labeled information and instead exploit the fact that anomalous behaviors tend to differ greatly from the standard or normal behavior of the network. Fiore et al [24] made use of discriminative restricted Boltzmann machine (RBM) for anomaly detection on network data; while Mirsky et al [25] proposed an ensembles of light-weight autoencoders for real time network intrusion detection, although their focus is on scalability of the system. Further, An and Cho [26] demonstrated that the VAE performs much better than AE and PCA on handwritten digit recognition and network intrusion detection.…”
Section: Related Workmentioning
confidence: 99%
“…However, the VAE model was trained using data labeled as normal, i.e., the anomalies are removed from training, which is difficult to do in practice. The above [24], [25], [26] are also known as semi-supervised learning.…”
Section: Related Workmentioning
confidence: 99%
“…The domain of using machine learning has been extensively researched in the past [6], and several scholarly papers on intrusion detection by data-mining techniques and machine intelligence have been published [10]. However, most of these prior studies have only used machine learning techniques for intrusion detection in traditional networks.…”
Section: Related Workmentioning
confidence: 99%